ANALYSIS OF INTEREST IN CONTINUING EDUCATION TO HIGHER EDUCATION AMONG VOCATIONAL SCHOOL STUDENTS IN ACCOUNTING: THE ROLE OF PARENTS, SCHOOLS, AND STUDENT READINESS - Haris, Nurul Hanifa; Susanti, Santi; Fauzi, Achmad (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
This study aims to determine whether there is an influence between parental support, the role of the school, and student readiness on the interest in continuing education to college. The population in this study were students majoring in accounting at Public Vocational High School in Central Jakarta, with an accessible population of 177 students. The sampling technique in this study used proportional random sampling with a sample of 122 respondents. The method used in this study is quantitative using questionnaires and surveys. The analysis methods in this study are descriptive statistical tests, validity tests, reliability tests, normality tests, linearity tests, multiple regression tests, hypothesis tests (t-test and f-test), and determination coefficient tests. The results of the research state that parental support has a significant effect on the interest in continuing education to college, the role of the school has a significant effect on the interest in continuing education to college, student readiness has a significant effect on the interest in continuing education to college, and parental support, the role of the school, and student readiness have a significant effect on the interest in continuing education to college.